Is Occupational Irritant Contact Dermatitis Predictable by Cutaneous Bioengineering Methods? Results of the Swiss Metalworkers’ Eczema Study (PROMETES) - Berndt, U.; Hinnen, U.; Iliev, D.; Elsner, P. (Dermatology (Basel), 1999)
Background: Since identification of subjects with high eczema risk by screening tests is desirable, different skin bioengineering methods were studied for their validity as predictive measures for the development of hand eczema. Methods: 205 metalworker trainees were followed up over 2.5 years from the beginning of their apprenticeship to observe the occurrence of hand eczema. Within the first weeks of their training they underwent a number of noninvasive biophysical tests. Transepidermal water loss, skin moisture and skin roughness were measured, and irritation tests with dimethyl sulfoxide (DMSO), sodium hydroxide (NaOH) and sodium lauryl sulfate were conducted. Sensitivity, specificity and predictive values of the performed tests and test combinations were calculated. Results: None of the observed single biophysical methods can be considered a valid screening test. Conclusion: A combination of short irritation tests (DMSO and NaOH tests) and the measurement of skin moisture, however, allows to identify individuals at high risk for hand dermatitis with a high sensitivity, though low specificity.